Quality Control Analysis of Carica Products Based on Sugar Content Parameters in PT AHA, Central Java - Mardiyanti, Nurul; Juwitaningtyas, Titisari; Metaragakusuma, Andi Patiware (Universitas Ahmad Dahlan, 2022)
PT AHA is a manufacturing industry company engaged in the processing of carica fruit food in the form of candied syrup (carica in syrup). On PT AHA every day will be carried out quality control to control the quality of carica in syrup. This study contributes to investigating the sugar content of carica in syrup. The sugar level was analyzed using a refractometer, dropper pipette, and toothpick, then the data obtained was analyzed using the SPC method (Statistical Process Control) and this test was carried out for 19 days. The results showed that there were 4 product samples outside the quality control limits, namely day 1 (22.1% Brix), day 6 (21.8% Brix), day 9 (18.3% Brix) and day 13(22.0 %Brix). Only 1 sample is found that exceeds the quality control limit, namely on day 1, while the others are still under control. The difference in sugar content in carica products is possible because when entering sugar using a manual scale, errors can occur when reading the weight.